2015
DOI: 10.1007/s00167-015-3767-5
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of 25 and 50 % subscapularis tears: a single anchor with a double-mattress suture is sufficient for the reconstruction

Abstract: A single double-loaded suture anchor provides sufficient biomechanical strength even in Fox/Romeo grade III tears of the subscapularis tendon. However, a modified suture configuration is recommended, especially in grade III tears as the suture-tendon interface is the weakest point of the construct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 44 publications
2
28
4
Order By: Relevance
“…(455 N). Regarding the amount of the measured maximal failure load, our results differed from those of Lorbach et al [36]; the specimens in our study that were treated with a knotted reconstruction technique had a higher maximal failure load than those from the study by Lorbach et al [36]. This difference can be explained by the different way in which the subscapularis tendon was fixed in the testing machine.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…(455 N). Regarding the amount of the measured maximal failure load, our results differed from those of Lorbach et al [36]; the specimens in our study that were treated with a knotted reconstruction technique had a higher maximal failure load than those from the study by Lorbach et al [36]. This difference can be explained by the different way in which the subscapularis tendon was fixed in the testing machine.…”
Section: Discussioncontrasting
confidence: 99%
“…This difference can be explained by the different way in which the subscapularis tendon was fixed in the testing machine. Although the force transmission from the muscle clamp was directly transferred to the subscapularis tendon in our study, Lorbach et al [36] used a tape between the clamp and the subscapularis. Dyrna et al [21] found that a double-row technique using a superolaterally placed anchor resulted in a higher load to failure than did a conventional single-row technique regardless of the defect size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Although there have been various proposals for the number of anchors needed for various tears, a biomechanical study determined that a single anchor for subscapularis tears that involved up to 50% of the subscapularis tendon provided adequate stability and fixation. 35 This surgical technique and accompanying technical video demonstrates an efficient repair for a complete, upper-third subscapularis tendon tear using a single knotless, soft-suture anchor through a single anterior working portal. Some advantages include providing the physician with the ability to provide tension to the repair under direct visualization after anchor insertion, avoiding potential complications associated with e4 traditional suture anchors, and obtaining overall time efficiency because surgical instruments that are typically involved with the use of traditional suture anchors are not required.…”
Section: Discussionmentioning
confidence: 98%
“… 34 Although there have been various proposals for the number of anchors needed for various tears, a biomechanical study determined that a single anchor for subscapularis tears that involved up to 50% of the subscapularis tendon provided adequate stability and fixation. 35 …”
Section: Discussionmentioning
confidence: 99%